The Position of Islamic Jurisprudence on Discipline by Social Penalties - Alshari, Hana'a; Etoum, Niebal (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: The study aims to establish the concept of communal sanctions in the system of punishment in Islamic jurisprudence, outline the criteria for their application, explore their relationship with similar systems, and demonstrate their practical application in Jordanian criminal law. Methods: The study adopts a descriptive methodology that includes both inductive procedures by tracing the jurisprudential issues and texts related to communal sanctions, referring to their original sources in Islamic jurisprudential books and principles, and analytical procedures involving the analysis of texts and evidence mentioned by jurists in the foundational issues of communal sanctions, as a means to derive conclusions. Results: The study concludes that communal sanctions are legitimate punishments that fall under the category of retributive punishments, aligning with Islamic criminal policy and not conflicting with any legal text; rather, there are indirect textual evidences supporting their legitimacy. The results also reveal that these sanctions have been adopted and implemented in Jordanian criminal law. Furthermore, they are subject to the concept of mitigating circumstances in Islamic law. Both precautionary measures and communal sanctions are categorized under retributive punishments. When applying communal sanctions, the criteria of retributive punishments are considered, and suitable elements are added to adapt them as alternative punishments. Conclusions: The study demonstrates that classical and contemporary jurists did not limit retributive punishments to specific types of sanctions but allowed for the introduction of new forms of retributive punishments, including communal sanctions, as one of the innovative types.